Subphthalocyanine-polymethine cyanine conjugate: An all organic panchromatic light harvester that reveals charge transfer - Nieto, Carlos Romero; Guilleme, Julia; Villegas, Carmen; Luis Delgado, Juan; Gonzalez-Rodriguez, David; Martin, Nazario; Torres, Tomas; Guldi, Dirk Michael (Journal of Materials Chemistry, 2011)
The synthesis and photophysical characterization of a subphthalocyanine- polymethine cyanine panchromatic light harvester is described. The new conjugate shows the extraordinary absorption features of both constituents and reveals electron transfer that evolves from both constituents. © 2011 The Royal Society of Chemistry.